Playing Multiple Positions - Landy Di Lu; Kathryn L. Heinze; Sara Soderstrom (University of Kansas Libraries, 2018)
Student-athletes enact dual roles, as students and athletes, and hold corresponding identities. The salience of these identities and conflict between them have implications for student-athlete wellness. The purpose of this study was to (a) gain insight into organizational and individual characteristics associated with identity salience, by examining student-athletes across universities; and (b) shed light on situations of identity salience and conflict for student-athletes. We conducted a survey study of student-athletes across 17 universities that captured both quantitative and qualitative data. Our results reveal a relationship between identity salience and individual performance (academic and athletic) and university ranking. Further, we found an interaction between athlete and student identity salience, such that identifying strongly as a student, athlete, both, or neither has implications for conflict. Finally, by unpacking situations of identity salience and conflict, we show similarities and differences across student-athletes' experiences. This study has implications for universities and athletic departments.